Process improvement methodologies uncover unexpected gaps in stroke care. (September 2018) - Kuner, Anthony D; Schemmel, Andrew J; Pooler, B Dustin; Yu, John-Paul J
Background: The diagnosis and treatment of acute stroke requires timed and coordinated effort across multiple clinical teams. Purpose: To analyze the frequency and temporal distribution of emergent stroke evaluations (ESEs) to identify potential contributory workflow factors that may delay the initiation and subsequent evaluation of emergency department stroke patients. Material and Methods: A total of 719 sentinel ESEs with concurrent neuroimaging were identified over a 22-month retrospective time period. Frequency data were tabulated and odds ratios calculated. Results: Of all ESEs, 5% occur between 01:00 and 07:00. ESEs were most frequent during the late morning and early afternoon hours (10:00–14:00). Unexpectedly, there was a statistically significant decline in the frequency of ESEs that occur at the 14:00 time point. Conclusion: Temporal analysis of ESEs in the emergency department allowed us to identify an unexpected decrease in ESEs and through process improvement methodologies (Lean and Six Sigma) and identify potential workflow elements contributing to this observation.